SOME COMPONENTS OF CHYME AND THEIR METABOLISM IN THEBODYPIGLETS - Мироненко, О. І. (Scientific Progress & Innovations, 2014)
The peculiarities of the digestive system in piglets after weaning, justified the use of certain non-conventional feed additives in the diets of pigs. The dynamics of the mineral elements (calcium, phosphorous, potassium, sodium, iron) and their metabolism in the gastrointestinal tract of pigs by the action of certain feed additives. The results of studies of dry feed additives mineral concentrate, Liprot and Echinacea purpurea in terms of their influence on the contents of the stomach empty and ileum.